PENGGUNAAN PENDEKATAN PAIKEM UNTUK MENINGKATKAN HASIL BELAJAR SENI RUPA DI KELAS VII SMPN 35 PADANG - YETRI YUNITA, Dra. Ernis, M.Pd. (Serupa The Journal of Art Education, 2019)
The purpose of this study is to improve student learning outcomes in art subjects through the use of the PAIKEM Approach in class VII-5 of SMP Negeri 35 Padang with learning materials on decorative materials in textile materials.The type of research that researchers use is Class Action Research (CAR). PTK is a form of research that is relational in nature by carrying out certain actions in order to improve and improve classroom practice so that teachers can be more confident in developing their own knowledge and skills.This research was conducted in two cycles. The data collection tool uses teacher observation sheets, student observation sheets, teacher activity sheets, student activity sheets, student activity assessment formats and student learning outcomes assessment formats.Reflections on the results of the study will be used as guidelines to determine whether or not the next cycle is needed. Data processed based on percentage formula. From the results of the study there are results of data processing which shows that there is an increase in student learning outcomes.The results of the action in Cycle I were 71.43%. While in Cycle II it increased to 82.81%. These findings illustrate the existence of an increase in student learning outcomes by 11.37%. So, this proves that using the PAIKEM Approach can improve the learning outcomes of Fine Arts.Keywords: PTK, Learning, PAIKEM Approach, Learning Outcomes.